Drivers of social capital in enhancing team knowledge sharing and team performance: moderator role of manager's cultural intelligence. (4th January 2021) - Thomas, Asha; Cillo, Valentina; Caggiano, Valeria; Vrontis, Demetris
In the contemporary global-village circumstances, multinational companies are reliant on their teams for creativity, productivity, etc. to compete with indecisive and cut-throat business surroundings. These multinational companies can opt for sharing knowledge of different teams from distinct countries. They are competent in attaining, employing, and expanding this knowledge. Because of this, there are mass cultures available in most workplaces. With globalisation, many new challenges like cultural diversity management have cropped up for people and firms. Individual as well as team performance can be enhanced by knowledge sharing. In active organisations, the diverse workforce might also be a planned factor for adding to knowledge resources. Very few researches have been carried out on the new concept, cultural intelligence (CQ).